The effect of Lactobacillus plantarum and Lactobacillus acidhophilus on cow milk and soy milk fermented - Wandeg Dasmar (Medical Laboratory Analysis and Sciences Journal, 2020)
This study aims to determine the effect of Lactobacillus Plantarum and Lactobacillus Acidhophilus Bacteria on Probiotic Beverage (Yogurt) from Cow's Milk and Soy's Milk, making yogurt is done by randomized design of groups factorially arranged using Lactobacillus plantarum. The second factor is the proportion of cow's milk and soy milk served at, namely: 100% cow's milk (S1), 50% cow's milk and 50% soy milk (S2) and 100% soy milk (S3) with the treatment applied through, addition lactic acid and viscystas from yogurt. Analysis results obtained from the addition of lactic acid. The proportion of cow's milk and soybean milk showed that Lactobacillus plantarum obtained a total of Lactic Acid of 0.45 and Lactobacillus acidhophilus. The proportion of Cow's Milk and Soymilk obtained a total Lactic Acid of 0.35. And the results of the analysis obtained from the Viscosity Proportion of Cow's Milk and Soybean Milk show that Lactobacillus plantarum obtained a total viscosity of 1.5 and Lactobacillus acidhophilus Proportion of Cow's Milk and Soybean Milk obtained a viscosity of 2.9.Keywords: influence, lactobacillus plantarum and lactobacillus acidhophilus, cow's milk and soy milk